2016
DOI: 10.1111/apt.13864
|View full text |Cite
|
Sign up to set email alerts
|

Review article: mesenchymal stromal cell therapy for inflammatory bowel diseases

Abstract: SUMMARY BackgroundInflammatory bowel diseases (IBD) are chronic relapsing diseases in which pro-inflammatory immune cells and cytokines induce intestinal tissue damage and disability. Mesenchymal stromal cells (MSCs) exert powerful immunomodulatory effects and stimulate tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 153 publications
0
80
0
Order By: Relevance
“…The immunosuppressive capacity of MSC allows tolerance in transplantation, while their potential to induce regeneration of damaged tissues and cell differentiation make them an effective tool for treating IBD [18]. Indeed, several clinical trials have shown short-term positive results in more than 200 nonresponsive patients with refractory IBD, in which MSC promoted a complete clinical remission in approximately 40% and an overall response in approximately 60% (for review, see Grégoire et al [19]). These effects involve T reg recruitment and T helper type 1 (Th1)/Th17 inhibition [19][20][21][22][23][24][25].…”
Section: Clinical and Experimental Immunologymentioning
confidence: 99%
See 3 more Smart Citations
“…The immunosuppressive capacity of MSC allows tolerance in transplantation, while their potential to induce regeneration of damaged tissues and cell differentiation make them an effective tool for treating IBD [18]. Indeed, several clinical trials have shown short-term positive results in more than 200 nonresponsive patients with refractory IBD, in which MSC promoted a complete clinical remission in approximately 40% and an overall response in approximately 60% (for review, see Grégoire et al [19]). These effects involve T reg recruitment and T helper type 1 (Th1)/Th17 inhibition [19][20][21][22][23][24][25].…”
Section: Clinical and Experimental Immunologymentioning
confidence: 99%
“…Indeed, several clinical trials have shown short-term positive results in more than 200 nonresponsive patients with refractory IBD, in which MSC promoted a complete clinical remission in approximately 40% and an overall response in approximately 60% (for review, see Grégoire et al [19]). These effects involve T reg recruitment and T helper type 1 (Th1)/Th17 inhibition [19][20][21][22][23][24][25]. Nevertheless, despite these well-described short-term properties, little is known about long-term MSC effects on IBD.…”
Section: Clinical and Experimental Immunologymentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, a growing number of diseases can be improved via wide applications of stem cell transplantation, such as congenital cataract [12], diabetic retinopathy and keratopathy [13], myocardial infarction [14], ocular surface burns [15, 16], serious skin burns [17, 18], Parkinson's disease [19], Huntington's disease [20], and especially DFU [21]. Accumulating evidence has pointed out that mesenchymal stem cells (MSCs) may enhance wound healing [2224] and be served as a cell source for many tissue engineering applications including bone regeneration [25], cartilage regeneration [2628], myocardial regeneration [29], neurogenesis [30, 31], inflammatory bowel diseases [32], and DFU [33, 34]. MSCs exist in many tissues, for example, bone marrow [35, 36], umbilical cord [37, 38], placenta [39, 40], adipose tissue [36, 4143], gingiva [44, 45], oral mucosa [46], amniotic fluid [47], and brain [48].…”
Section: Introductionmentioning
confidence: 99%